Evaluation Report on Working of Community Projects and N.E.S. Blocks, Government of India - Planning Commission (Planning Commission, 1956)
The community development programme is now in its fourth year. The first 55 community projects which stirred the imagination of the country are now in their closing stages. The intervening years have seen the transformation of the programme from an experiment initiated in a few areas to a nation-wide programme of rural development. The pattern of the national extension service has been accepted as the basic pattern of rural development administration an the welfare State and it is proposed to extend it over the whole country during the Second Plan period. Besides, a very large area will receive the intensive development effort under the community ’project phase. The content and the methods of the programme have undergone considerable change since the first projects started, further changes will continue to be made as new problems arise and especially as the scope of the programme widens to make up the deficiencies noted and to include those sections of the rural population which had not been adequately benefited before. The Evaluation Reports, ’attempting as they do, a review of the progress of the programme in terms of its objectives are a contribution towards this process, of making the content of the programme more meaningful, and its methods more closely related to its objectives.
Evaluation Report
Government of India